2012
DOI: 10.1021/ja309760g
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Profiling of Peptide–RNA Interactions Using Peptide Microarrays

Abstract: A rapid and quantitative method to evaluate binding properties of hairpin RNAs to peptides using peptide microarrays has been developed. The microarray technology was shown to be a powerful tool for high-throughput analysis of RNA-peptide interactions by its application to profiling interactions between 111 peptides and six hairpin RNAs. The peptide microarrays were also employed to measure hundreds of dissociation constants (K(d)) of RNA-peptide complexes. Our results reveal that both hydrophobic and hydrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…The peptides used in this study were synthesized on a solid support employing a conventional Fmoc/t-Bu strategy (Supplementary Table S8)36. Binding of the Mad1 and SAP25 peptides to mouse Sin3A PAH1 (residues 114–195) and PAH2 (residues 295–385) was determined using fluorescence polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The peptides used in this study were synthesized on a solid support employing a conventional Fmoc/t-Bu strategy (Supplementary Table S8)36. Binding of the Mad1 and SAP25 peptides to mouse Sin3A PAH1 (residues 114–195) and PAH2 (residues 295–385) was determined using fluorescence polarization.…”
Section: Resultsmentioning
confidence: 99%
“…5 It has been implicated that the internal residues of the peptide 1 is associate with RNA binding. 5 We deleted three amino acids at the C-terminus of peptide 1 and made a truncated construct of peptide 1' (LKKLLKLLKKLLK) to characterize the tertiary interaction between the peptide 1' and HCV IRES domain IV. In the protein-free form of HCV IRES, the domain IV forms a small hairpin where the start codon AUG is located at the apical loop ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…4 Previously, an L-and K-rich peptide that strongly binds to the HCV IRES domain IV hairpin was reported. 5 Here, we report further structural characterization of the tertiary interaction between the peptide and HCV IRES domain IV RNA using NMR methods. The chemical shift perturbation (CSP) studies indicate that the peptide preferably binds to the upper stem of the IRES RNA, suggesting that this peptide would inhibit the denaturation of the domain IV hairpin structure.…”
Section: Introductionmentioning
confidence: 95%
“…23,24 Furthermore, previous studies have shown that amphiphilic α-helical peptides can selectively and strongly bind to hairpin RNAs. 25,26,27 In accordance with this idea, we hypothesized the existence of peptide(s) that can affect miR29 expression by up-regulating p53 activity in cancer cells.…”
Section: Introductionmentioning
confidence: 86%